The God of Difference Disability, Youth Ministry, and the Difference Anthropology Makes - Raffety, Erin (2018)
In their eagerness to love and care for young people with disabilities, youth ministers and lay people have often failed to appreciate the challenge of human difference. The author shows that studies in youth ministry struggle to hold in tension differences in culture, developmental categories, and disability among youths, often dismissing these differences as oppositional to Christian relationship or community. Drawing on cultural anthropology, humble, embodied attention to the situated character of knowledge can help both scrutinize and regard difference. Embracing difference as a spiritual discipline in ministry with youths with disabilities enables participation in the different, disruptive ministry of Christ.
Keywords: Disability; Cultural Anthropology; Culture; developmental categories; Difference; Youth Ministry